2018
DOI: 10.3390/agriculture8050066
|View full text |Cite
|
Sign up to set email alerts
|

Salt Tolerance of Six Switchgrass Cultivars

Abstract: ') were evaluated for salt tolerance in two separate greenhouse experiments. In experiment (Expt.) 1, switchgrass seedlings were irrigated with a nutrient solution at an electrical conductivity (EC) of 1.2 dS•m −1 (control) or a saline solution (spiked with salts) at an EC of 5.0 dS•m −1 (EC 5) or 10.0 dS•m −1 (EC 10) for four weeks, once a week. Treatment EC 10 reduced the tiller number by 32% to 37% for all switchgrass cultivars except 'Kanlow'. All switchgrass cultivars under EC 10 had a significant reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…In roots, Alamo showed a lower Na concentration in the 300 mM treatment that could be explained by a reduction in Na influx to the roots or an efflux increase via a salt overlay sensitive (SOS) pathway [52]. Conversely, Sun et al [34] described a higher Na concentration in Alamo compared to five other switchgrass genotypes including Kanlow. In our study, both Kanlow and Trailblazer accumulated a high concentration of Na in shoots, although the concentration of Na was almost double in the stems of Trailblazer.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In roots, Alamo showed a lower Na concentration in the 300 mM treatment that could be explained by a reduction in Na influx to the roots or an efflux increase via a salt overlay sensitive (SOS) pathway [52]. Conversely, Sun et al [34] described a higher Na concentration in Alamo compared to five other switchgrass genotypes including Kanlow. In our study, both Kanlow and Trailblazer accumulated a high concentration of Na in shoots, although the concentration of Na was almost double in the stems of Trailblazer.…”
Section: Discussionmentioning
confidence: 95%
“…After 75 days of salt stress exposure (135 DAP), there was evidence of a direct effect of salinity (50 and 100 mM) on shoot biomass, which was more evident in the lowland genotypes Alamo and Kanlow. Previous studies have shown that 30 days of exposure to 250 mM NaCl [26], 30 days of irrigation with 10.0 dS m −1 saline solution [34] or 60 days at~180 mM NaCl [35] can impact the biomass yields in switchgrass. To our knowledge, however, there are no studies on the effect of lower concentrations (50 and 100 mM NaCl), although similar responses have been observed in Miscanthus, with significant yield-reductions after a 64-day salinity exposure to concentrations of 100 mM NaCl [36].…”
Section: Discussionmentioning
confidence: 99%
“…High soil salinity negatively affects seed germination, seedling emergence and growth, and it modifies a plant's physiological and biochemical processes (Kim et al, 2012; Sun et al, 2018). There is a large area of land in the Loess Plateau that is plagued by soil salinity and sodium, and thus it is not suitable or not profitable for planting economic crops (Cooney et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…A range of genetic variation for biomass yield under salinity stress conditions among switchgrass cultivars has been reported (S. Kim et al, 2012;J. Kim et al, 2016;Anderson et al, 2015;Sun et al, 2018). Salinity tolerance in plant species is recognized as a quantitative trait (Singh et al, 2007;Joseph et al, 2010;Lang, Xu et al, 2017).…”
Section: Core Ideasmentioning
confidence: 99%
“…Salinity may cause low to severe damage to plant growth and survivability, depending upon plant species and the amount of salt present in the soil. Salinity can cause a substantial reduction in seed germination, seedling emergence, seedling growth, and biomass yield of switchgrass (Sun et al, 2018). Therefore, identifying salt-tolerant switchgrass genotypes and improving cultivars to have an increased level of salt tolerance is very important for maximum utilization of salt-affected lands.…”
Section: Crop Sciencementioning
confidence: 99%